ANALYSIS OF THE ROLE OF DIGITAL LITERACY IN OPTIMIZING SOCIAL MEDIA MARKETING BY STUDENT ENTREPRENEURS AT SATYAGAMA UNIVERSITY - Didi Sukardi; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Murdiyono Murdiyono (Yayasan Nusantara Hasana Berdikari, 2023)
The development of digital technology has encouraged students to utilize social media as a marketing tool for their businesses. This study aims to analyze the role of digital literacy in optimizing social media marketing among student entrepreneurs at Satyagama University. The research method used was a quantitative approach, distributing questionnaires to students who have active businesses and use social media for promotion. The results show that digital literacy skills have a positive effect on digital marketing effectiveness, particularly in content creation, consumer communication, and increasing market reach through social media platforms.